2014
DOI: 10.12816/0006068
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Environmental and Agricultural Pollutants on the Prevalence of Allergic Diseases in People from Qassim , KSA

Abstract: Background: There are multiple environmental factors that influence a sensitized (IgE antibody positive) patient's predisposition to manifest allergic symptoms following allergen exposure. The majority of allergens are known to induce morbidity with chronic symptoms such as rhinitis, pruritis, dermatitis and urticaria. Aim:To study the impact of environmental and agricultural pollutants with different pollens on the immunological, hematological and biochemical markers and to determine the prevalence of sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
1
4
1
Order By: Relevance
“…It is of major concern that the nasal epithelial cells of nonallergic subjects reacted via an inflammatory response to the combination of NO 2 and Der p 1, which may be an initial step in allergen sensitization. These findings are in line with the environmental studies of Elshabrawy et al [29], and to our knowledge this is the first in vitro study to analyze the impact of volatile air pollution on human cellular reactions to aeroallergens. …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is of major concern that the nasal epithelial cells of nonallergic subjects reacted via an inflammatory response to the combination of NO 2 and Der p 1, which may be an initial step in allergen sensitization. These findings are in line with the environmental studies of Elshabrawy et al [29], and to our knowledge this is the first in vitro study to analyze the impact of volatile air pollution on human cellular reactions to aeroallergens. …”
Section: Discussionsupporting
confidence: 91%
“…Studies considering a synergistic effect of both a major allergen and a volatile reactive gas are rare. A recent study by Elshabrawy et al [29] examined the impact of environmental and agricultural pollutants on the prevalence of allergic diseases. The authors demonstrated that subjects which are highly exposed to environmental and agricultural pollution are at a high risk for developing allergies.…”
Section: Discussionmentioning
confidence: 99%
“…The clinically relevant prevalence of mango allergy was 0.29%. This prevalence was lower compared to Shaoguan, China (1.4%) [45], Taiwan, China (18.5%) [20], and Japan (12.5%) [21]. Apple allergy in our study was confirmed in 0.1% of the patients.…”
Section: Discussioncontrasting
confidence: 52%
“…Mango and apple allergy are rare in European countries but are common in China and some other countries of East Asia. Data have shown that the mango allergy rate in Taiwan, China [20] is 18.5%, and 12.5% in Japan [21]. The incidence of apple allergies is lower compared to mango allergies, but anaphylactic shock is often reported [22].…”
Section: Introductionmentioning
confidence: 99%
“…All insect matter like wings, scales, saliva, dried fecal matter, and venom can cause allergic diseases such as rhinitis, conjunctivitis, asthma, urticaria and gastric disorders 14,15 . Depending on the route of sensitization, the insect allergens have been recognized as an inhalant, ingestant and injectant allergens 16.…”
Section: Bacallergy and Insectmentioning
confidence: 99%